Technology in Agriculture 2021
DOI: 10.5772/intechopen.97301
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption-Based Atmospheric Water Harvesting: Technology Fundamentals and Energy-Efficient Adsorbents

Abstract: Nowadays, atmospheric water harvesting (AWH) became very essential to provide fresh potable water. This technique is in practice since 1900 (US661944A) by Edger S. Belden. Atmospheric water is a source of freshwater with 13000 trillion liters availability of water at any time and can be utilized in overcoming water shortage, especially in arid and rural areas. It holds up the water molecules in the form of vapors and accounts for adding 10% of all freshwater present on the earth. Mainly, the two most common me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…However, these methods heavily rely on the presence of liquid water sources and face significant limitations in regions that are landlocked 5 , 6 . It is a well-established fact that freshwater on Earth also includes water vapor present in the atmosphere, amounting to a total of 15 trillion liters 7 , 8 . Surprisingly, even in landlocked regions, a significant amount of water vapor exists.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods heavily rely on the presence of liquid water sources and face significant limitations in regions that are landlocked 5 , 6 . It is a well-established fact that freshwater on Earth also includes water vapor present in the atmosphere, amounting to a total of 15 trillion liters 7 , 8 . Surprisingly, even in landlocked regions, a significant amount of water vapor exists.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, adsorption-based AWH technology offers a relatively cost-effective, environment-friendly, decentralized technique that operates with low-grade thermal energy. To date, adsorption-based AWH has gained renewed interest by researchers and practitioners due to its adaptability and mobility [18][19][20][21]. Primarily, this review presents the most updated view regarding the adsorption-based AWH technologies on both system design and the adsorbent materials.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, Ghisi et al [4,5] showed that the use of rainwater could potentially result in a 92% peak saving in potable water use. Additional potential sources of harvesting potable water from different sources include atmospheric water harvesting and other sources [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Gitte and Pendke [23] studied water conservation practices, water table fluctuations, and groundwater recharge in watershed areas.…”
Section: Introductionmentioning
confidence: 99%